Is peer review in academic publishing still working?*. Issue 1 (1st January 2018) - Jackson, Liz; Peters, Michael A.; Benade, Leon; Devine, Nesta; Arndt, Sonja; Forster, Daniella; Gibbons, Andrew; Grierson, Elizabeth; Jandrić, Petar; Lazaroiu, George; Locke, Kirsten; Mihaila, Ramona; et al.
ABSTRACT: Peer review is central to academic publishing. Yet for many it is a mysterious and contentious practice, which can cause distress for both reviewers, and those whose work is reviewed. This paper, produced by the Editors' Collective, examines the past and future of peer review in academic publishing. The first sections consider how peer review has been defined and practised in changing academic contexts, and its educational significance in the development of scholarship. The paper then explores major historical and contemporary issues around identity, diversity, anonymity, and the review process, and the related power of editors versus reviewers in academic publishing. Finally, the paper discusses the case of new scholars as reviewers engaging in neoliberal labour, before concluding with some brief recommendations based on our analysis.